2022
DOI: 10.1111/jog.15335
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic association and prognostic impact of microcystic, elongated and fragmented pattern invasion, combined with tumor budding in endometrioid endometrial cancer

Abstract: Aim As a special invasive pattern seen in low‐grade endometrial carcinoma, microcystic, elongated and fragmented (MELF) pattern is related to lymph node metastasis. Tumor budding (TB) is another histological marker in many cancers associated with tumor aggressiveness. Herein, we evaluated the impact of MELF pattern combined with TB about clinicopathological features and prognosis in endometrioid endometrial cancer (EEC). To verify the relationship between the two morphological markers and microsatellite status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…These results are in line with previous publications reporting inferior outcomes for tumors with high TB compared to tumors with low TB for several tumor entities like colorectal adenocarcinomas, head and neck squamous cell carcinomas and non-small cell lung cancer [17]. Up to date, there are only a few publications reporting inferior outcomes of patients with high TB in endometrial cancer [19,20]. In general, TB is supposed to be associated with at least partial epithelial to mesenchymal transition (EMT), causing cancer invasion and leading to lymph node metastases and distant metastases [44].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in line with previous publications reporting inferior outcomes for tumors with high TB compared to tumors with low TB for several tumor entities like colorectal adenocarcinomas, head and neck squamous cell carcinomas and non-small cell lung cancer [17]. Up to date, there are only a few publications reporting inferior outcomes of patients with high TB in endometrial cancer [19,20]. In general, TB is supposed to be associated with at least partial epithelial to mesenchymal transition (EMT), causing cancer invasion and leading to lymph node metastases and distant metastases [44].…”
Section: Discussionsupporting
confidence: 91%
“…As Qi. et al [20] previously proposed a grading system including MELF and TB, we included these parameters (TB and MELF) in a subsequent multivariate analysis to probe their independent impact in a Cox regression model. Here, only TB was shown to be an independent variable (HR: 12.19, p < 0.001, Supplementary Table S6).…”
Section: Cnlowmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep learning model successfully flagged these subtle regions, alerting pathologists to re-examine the case. MELF invasion was an independent prognostic factor closely related to the risk of lymph node metastasis ( 28 ), indicating poor prognosis. Omitting deep muscular infiltration leads to a lower stage (from IA2 to IA1).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Qi et al 2 demonstrated that the combination of MELF and tumor budding is a histological marker associated with tumor aggressiveness and can be an independent predictor of adverse outcomes. Moreover, Tahara et al 3 reported a strong expression of programed death-ligand 1 (PD-L1) in the invasive front of the MELF pattern and concluded that programed cell death protein 1/PD-L1 immunotherapy demonstrated significant therapeutic effect on the management of patients with endometrial cancer and grade 1 MELF.…”
mentioning
confidence: 99%